Corrosion Inhibition Efficiency of Benzimidazole and Benzimidazole Derivatives for Zinc, Copper and Brass - Yanardag, T.; Ozbay, S.; Dincer, S.; Aksut, A.A. (Asian Journal of Chemistry, 2011)
In this study, 1H-benzimidazole, (BIM), 2-methyl-1H-benzimidazole (2-CH3BIM), 5-nitro-1Hbenzimidazole [5(6)-NO2BIM] and 5(6)-dinitrobenzimidazole (5,6-diNO2BIM) were investigated as corrosion inhibitors of copper, zinc and brass in alkaline and neutral media. The inhibition efficiency was calculated by using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The frequency range studied was 1×105 -1×10-1 Hz. Surface of the zinc, cupper and brass electrodes were polished with sand paper and etched in 0.15 M HCl solution for 20 s and than immersed in study solutions. Under the experimental conditions, the efficiency of these inhibitors increases in the order BIM > 5(6)-NO2-BIM >5,6-diNO2BIM >2-CH3-BIM in alkaline media (pH:13) and 2-CH3-BIM >5(6)-NO2-BIM > BIM in the 0.5 M NaCl the solution.